Assessing nurses’ knowledge, roles, and challenges in the management of non-communicable diseases in primary health care centres under emirates health services: A cross-sectional study - Dr. Hanan Mohamed Soliman; Reihab ElSaid Mohamed (International Research Journal of Public and Environmental Health, 2026)
Non-communicable diseases (NCDs), particularly cardiovascular diseases, diabetes, cancer, and chronic respiratory diseases, remain major public health concerns and contribute significantly to illness, disability, and premature mortality worldwide. In the United Arab Emirates (UAE), the growing burden of NCDs increases pressure on primary healthcare services and highlights the need for effective prevention, early detection, and long-term management. Nurses play an important role through screening, health education, counselling, lifestyle modification, treatment support, and follow-up. However, inadequate training, heavy workloads, and limited resources may affect their ability to provide effective care. This study assessed nurses’ roles, knowledge, and challenges in NCD management within Emirates Health Services (EHS) primary healthcare centres. A quantitative cross-sectional study was conducted between January and June 2025 among 308 nurses using an online self-administered questionnaire. Only 7.8% were diabetic nurse educators and 5.2% were NCD nurse specialists. Most nurses (62.01%) had low knowledge of NCD management, while 35.71% had sufficient and 2.27% had high knowledge. Practice levels were low for 42.21%, sufficient for 31.82%, and high for 25.97%. A significant difference was found between trained and untrained nurses (z = −4.12, p = 0.00004). Key challenges included administrative workload (78.25%), poor community awareness (74.68%), inadequate training (72.08%), and limited diagnostic tools (70.45%). Overall, the findings point to important gaps in nursing capacity for NCD management. Strengthening continuing professional development, reducing administrative demands, improving diagnostic resources, and promoting community awareness could enhance the quality and effectiveness of NCD services within EHS primary healthcare settings.